Maqāmāt Abī Zayd al-Sarūjī - al-Ḥarīrī (Book collections on Project MUSE., 2020)
Maqāmāt Abī Zayd al-Sarūjī is a scholarly, Arabic-only edition of the celebrated work by al-Ḥarīrī, which is also available in English translation from the Library of Arabic Literature as Impostures. This work consists of fifty stories about the adventures of the itinerant con man and master of persuasion Abū Zayd al-Sarūjī, as told by the equally itinerant and often clueless narrator al-Ḥārith ibn Hāmmam. Al-Ḥarīrī was a virtuoso writer of the rhymed prose narrative genre known as the maqāmah, which would continue as a popular literary form into the twentieth century.